2010
DOI: 10.4314/jasem.v12i1.55582
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Profile of Biodegraded Brewers Spent Grains (BSG)

Abstract: ABSTRACT:The aim of this was to study the nutritive value of urea and corn grain treated wheat straw ensiled with cattle manure. The different levels of urea (0, 2 and 4%) and corn grain (2 and 4%) were used to treat wheat straw. The urea-corn grain treated wheat straw was mixed with cattle manure in the ratio of 70:30. The silages were fermented in laboratory silos for 20, 30 and 40 days. After the completion of ensilation period, the samples of ensiled wheat straw were analyzed for pH, dry matter (DM), crude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…From the treated group, researchers obtained enhanced total milk and milk fat relative to the control group (Aliyu and Bala ), while the blood plasma concentrations of glucose, cholesterol, total protein, urea, albumin, sodium, and triacylglyceride (Itagaki and others) were not affected (Dhiman and others ; Mussatto and others ). Moreover, a contemporary study showed that biodegraded BSG contained lysine, methionine, cysteine, and 14 other amino acids (Essien and Udotong ). Among them, alanine was found to have the highest concentration, although all were important in the poultry diet.…”
Section: Use In Animal Feedmentioning
confidence: 99%
“…From the treated group, researchers obtained enhanced total milk and milk fat relative to the control group (Aliyu and Bala ), while the blood plasma concentrations of glucose, cholesterol, total protein, urea, albumin, sodium, and triacylglyceride (Itagaki and others) were not affected (Dhiman and others ; Mussatto and others ). Moreover, a contemporary study showed that biodegraded BSG contained lysine, methionine, cysteine, and 14 other amino acids (Essien and Udotong ). Among them, alanine was found to have the highest concentration, although all were important in the poultry diet.…”
Section: Use In Animal Feedmentioning
confidence: 99%
“…An analysis of the amino acid content in brewers grain showed a high amount of cysteine, lysine and methionine in addition to the presence of 14 other amino acids. This kind of composition indicates that brewers grain can be considered as an important component in poultry nutrition (Essien and Udotong, 2008). The inclusion of WBG to the diet of monogastric animals could also be beneficial for intestinal digestion, alleviating both constipation and diarrhea.…”
Section: Introductionmentioning
confidence: 97%
“…The authors attributed this enhanced growth performance to the high-quality protein contained in the waste grains. A more recent study showed that biodegraded BSG contained cysteine, lysine and methionine in addition to fourteen other amino acids (74) . Depending on the microbe used to degrade the BSG, different amino acid concentrations were found, with alanine consistently at highest concentrations.…”
Section: Animal Foodmentioning
confidence: 99%